Gambaran Mikroskopik Berbagai Jenis Jaringan Pada Bakso - Diana A. Wuri (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The purpose of this study is to examine the meatball composition microscopically. Twelve commercial meatball samples marketed in Bogor were used in this study. All samples were processed for histopathology slides. The 5 m meatballs sections were stained with Gomori’s Chrome Alum Hematoxylin. Five (41.67%) of 12 samples showed parts of smooth muscle and cartilage within the meatball section. This findings did not comply with the Indonesian National Standard (SNI) regulation, that the meatball should contain only the skeletal muscle. This study showed that the microscopic tissue examination could be utilized as a tool for tissue types detection qualitatively in meatball.